Fish head in Italian and Croatian proverbs - Ljubičić, Maslina (2008)
The noun head has many metaphorical meanings, among others ‘ the highest or uppermost part or thing ; top’ , ‘ the foremost part of a thing’ , ‘ a position of leadership, honor, or first importance’ , ‘ person who is foremost or in charge ; leader, ruler, chief, director, etc.’ In many lexical collocations, idiomatic expressions and proverbs the head refers to the most important part or the ruling position. The proverb “ The fish always stinks from the head downwards” exists in many languages and is much used from antiquity to the present day. Taking this largely diffused proverb as a starting point, the paper will deal with those proverbs which are culturally much more specific. In particular, the paremiologic use of “ fish head” metaphor which appears in Italian and Croatian proverbs will be analysed. These proverbs are characteristic of seafaring people whose languages possess various semantically much more general intralinguistic and interlinguistic equivalents.